An evaluation of energy and carbon budgets in diverse cropping systems for sustainable diversification of rainfed uplands in India's eastern hill and plateau region - Pan, Rabi Sankar; Mali, Santosh S.; Kumar, Rakesh; Naik, Sushanta Kumar; Upadhyay, Pravin Kumar; Shinde, Reshma; Jha, Bal Krishna; Jeet, Pawan; Das, Anup (Frontiers in Sustainable Food Systems, 2024)
With increasing cost and use of energy in agriculture, the traditional practice of mono-cropping of rice in upland is neither sustainable nor eco-friendly. It is necessary to identify crop diversification options with high energy efficiency, productivity, and low global warming potential (GWP). In this experiment, an inclusive system analysis was accomplished for 3 years (2016–2019) of five mono-cropping production (MCP) systems namely rice (R), finger millet (FM), black gram (BG), horse gram (HG), pigeon pea (PP), and four intercropped systems viz. R+BG, R+HG, FM+ BG, and FM + HG. The key objective was to evaluate the flow of energy, carbon balance, and GWP of these varied production systems. Puddled rice was recorded as an energy-exhaustive crop (27,803 MJ ha−1), while horse gram was noted to have the lowest energy use (26,537 MJ ha−1). The total energy output from pigeon pea (130,312 MJ ha−1) and diversified intercropped systems (142,135 MJ ha−1) was 65.3% and 80.3% higher than mono-cultured systems, respectively. Rice and rice-based intercropping production systems showed higher carbon footprints (1,264–1,392 kg CO2 eq. ha−1). Results showed that R+BG and R+HG were the most energy-efficient production systems, having higher energy ratio (5.8 and 6.0), higher carbon efficiency (7.41 and 8.24), and carbon sustainability index (6.41 and 7.24) as against 3.30, 3.61, and 2.61 observed under sole cropping production systems. On average, rice and rice-based production systems had 7.4 times higher GWP than other production systems. In productivity terms, pigeon pea and FM+HG had higher rice equivalent yields of 8.81 and 5.79 t ha−1 and benefit-cost ratios of 2.29 and 1.87, respectively. Thus, the present study suggests that pigeon pea and finger millet-based intercropping systems were the most appropriate crop diversification options for the rainfed upland agro-ecosystem of the eastern region of India.